Akibat Hukum Pembatalan Perkawinan dalam Perspektif Hukum Perlindungan Anak dan Perempuan di Pengadilan Agama Sumatera Selatan - Sri Turatmiyah; M. Syaifuddin; Arfianna Novera (Fakultas Hukum Universitas Islam Indonesia, 2015)
This study discusses the factors causing the cancellation of the marriage in the Religious Court of Palembang, Lubuklinggau, Muaraenim and its legal consequences for the child and the wife. The study was conducted normatively supported by empirical evidences. The study concluded that first, in Decision No. 0587 / Pdt.G / 2013 / PA.Plg and 796 / Pdt.G / 2010 / PA.Llg contributing factor of marriage cancellation is unpermitted polygamy and unauthorized guardian. Secondly, the legal consequences for the child according to Article 28 of Marriage Law is that the child remain legitimate and for his wife in good faith, the marriage still posseses a legal effect which is valid for a husband and wife. If the marriage took place without the goodwill of the husband and wife, as a result of the marriage law it did not exist. The judges' decision is retroactive to when the marriage took place.